Illness among holidaymakers and the effect on a seaside practice. Issue 6481 (25th May 1985) - Maskrey, N; Poppleton, J F; Knowelden, D J; Grahame, L C
Abstract : Between 1 May and 30 September 1983 a practice of three doctors in the centre of Scarborough conducted 1772 consultations with 1472 temporary residents, 967 (55%) of which were during July and August. The pattern of illness differed considerably from that usually found in general practice, with an excess of minor infections, gastrointestinal upsets, and skin problems comprising 46% of the consultations. Practitioners who care for appreciable numbers of temporary residents should plan their services to match the special needs of holidaymakers. The task of doctors in areas with many visitors would be made easier if patients who are on regular medication or are under surveillance brought with them not only enough drugs for their needs but also a summary of their medical history.